In the distance eaudiobook - Diaz, Hernan (HighBridge Audio, 2017)
A young Swedish immigrant finds himself penniless and alone in California. The boy travels East in search of his brother, moving on foot against the great current of emigrants pushing West. Driven back again and again, he meets naturalists, criminals, religious fanatics, swindlers, Indians, and lawmen, and his exploits turn him into a legend. Diaz defies the conventions of historical fiction and genre, offering a probing look at the stereotypes that populate our past and a portrait of radical foreignness.